ANALYSIS CHLORIDE OF GROUND WATER WITH MULTIPLE REGRESSION IN AREAS BELAWAN CITY - Muzambiq, Said; Dodi Hary Sasmita, Bambang; Nurhayati (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
Water indispensable for all life forms and crucial for enhancing human well-being, faces threats from unsustainable groundwater abstraction practices. Ignoring soil water chemistry's characteristics and physical properties during groundwater extraction can lead to contamination, jeopardizing both the quality and quantity of groundwater resources. This contamination, resulting from natural processes like sedimentation and human activities such as sewage discharge, poses significant pollution risks. Through the analysis of chloride levels in groundwater, this study examines the intricate relationships between hydrochemical parameters and seawater intrusion. Utilizing multiple regression analysis, it establishes strong correlations between chloride concentration and key variables including water usage, well depth, permeability, and distance from the shoreline. Predictive curve graphs elucidate how these variables influence chloride concentrations, emphasizing the importance of managing groundwater resources sustainably. The research underscores the imperative of addressing the increasing demand for water while mitigating environmental risks, ensuring the availability of clean water resources for future generations.